The Strategy of TPA Educational (Al-Qur'an Educational Park) to Overcoming Noisy Attitudes Childrens in During Jum’at Prayer: a Phenomenon at Mesjit of Yogyakarta - Mgr Sinomba Rambe; Asep Yudianto; Fakhrul Mukmin; Syamsul Arifin; Munzir Munzir; Dakhliatunnaviah Dakhliatunnaviah (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2024)
This research aims to explore the educational strategy of the Al-Qur'an Education Park (TPA) in dealing with children's noise during Friday prayers at the Nur Sidik Mosque, Yogyakarta. Using a descriptive qualitative case study approach, data was collected through observations and interviews with TPA teachers as well as parents and TPA children. The research results highlight concrete strategies, which include interactive learning methods, special activities before Friday prayers, and the application of rewards and punishments that are in accordance with Islamic values. Close collaboration between TPA teachers, parents, and the community is key to creating a conducive environment for the implementation of worship, ensuring meaningful and solemn worship for children, especially in carrying out Friday prayers, and forming a golden generation with Islamic character and noble morals in social life.